Critical Theory Foundations of Digital Capitalism: A Critical Political Economy Perspective - Christian Fuchs (tripleC: Communication, Capitalism & Critique)
The overall task of this paper is to outline some foundations of a critical theory of digital capitalism. The approach of the Critique of Political Economy is taken as the starting point for theorising (digital) capitalism.